Competitiveness in Transition Economies : What Scope for Real Appreciation? - Krajnyak, Kornelia (IMF Working Papers; Working Paper ;, 1997)
This paper estimates equilibrium dollar wages for 15 transition economies. Equilibrium dollar wages are interpreted as full employment wages consistent with a country's physical and human capital endowment, and estimated by regressing actual dollar wages on productivity and human capital proxies in a short (1990-95) panel of 85 countries. The main results are: (i) equilibrium dollar wages have appreciated steadily in the Baltic countries and fast-reforming Central and Eastern European (CEE) transition economies, but have been flat in most CIS countries; and (ii) 1996 actual dollar wages remain below estimated equilibrium dollar wages for most but not all transition countries covered.